MESOSCALE WEATHER SIMULATIONS OF NORTHERN PERU (2015) USING BRAZILIAN REGIONAL ATMOSPHERIC MODELING SYSTEM (BRAMS) - Rubio, Obidio (2015)
The warm of the tropical pacific ocean generate the El Niño phenomenon. The Peru between the years 1997 and 1998 took big materials losses and human victims because the presence of EL NIÑO.Now the scientists try to make a prediction of the magnitude of natural phenomenon using different methods of simulation. Our objective are study the changes in the weather variables such that:temperature, wind fields and relative humidity, from October to November in 2015 and compared with years 1997 and 1998. We used the BRAMS (Brazilian Regional Atmospheric Modelling System) model; with this model We could analyze the differences of temporal and spatial changes for the weather variables. The variation of temperature in northern Peru was around 18 and 29 degreesCelsius , relative humidity was around 35 and 100% of the coast, the wind fields were 2.7 km/h to 9.9 km/h . The Temperature at regions of interest: Tumbes, Piura, Lambayeque and La Libertadpresented a decrease in 9, 5,6 and 6 degrees celsius from octuber to November, respectively. In conclusion, the weather variables have presented a decrease in November 2015, these behavior didnot occur in the years 1997 and 1998.